An Increase in Alpha Band Frequency in Resting State EEG after Electrical Stimulation of the Ear in Tinnitus Patients—A Pilot Study - Mielczarek, Marzena; Michalska, Joanna; Polatyńska, Katarzyna; Olszewski, Jurek (Frontiers in Neuroscience, 2016)
In our clinic invasive transtympanal promontory positive DC stimulations were first used, with a success rate of 42%. However, non-invasive hydrotransmissive negative DC stimulations are now favoured, with improvement being obtained in 37.8% directly after the treatment, and 51.3% in a follow up one month after treatment. The further improvement after one month may be due to neuroplastic changes at central level as a result of altered peripheral input. The aim of the study was to determine how a single electrical stimulation of the ear influences cortical activity, and whether changes observed in tinnitus after electrical stimulation are associated with any changes in cortical activity recorded in EEG. The study included 12 tinnitus patients (F–6, M-6) divided into two groups. Group I comprised six patients with unilateral tinnitus - unilateral, ipsilateral ES was performed. Group II comprised six patients with bilateral tinnitus - bilateral ES was performed. Electrical stimulation was performed using a custom-made apparatus.The active, silver probe – was immersed inside the external ear canal filled with saline. The passive electrode was placed on the forehead. The stimulating frequency was 250Hz, the intensity ranged from 0.14 to 1.08 mA. The voltage was kept constant at 3V. The duration of stimulation was four minutes. The EEG recording (Deymed QEST 32) was performed before and after electrical stimulation. We assessed the intensity of tinnitus on the visual analogue scale (1-10). Results. In both groups an improvement in VAS was observed – in group I - in five ears (83.3%), in group II - in seven ears (58.3%). In Group I, a significant increase in the upper and lower limits of the alpha frequency range was observed in the left central temporal and left frontal regions following electrical stimulation. These changes, however, were not correlated with improvement in tinnitus. No significant changes were observed in the beta and theta bands and in group II. Preliminary results of our research reveal a change in cortical activity after electrical stimulations of the ear. However, it remains unclear if it is primary or secondary to peripheral auditory excitation. No similar studies had been found